Risk assessment of arrhythmias related to three antiseizure medications: a systematic review and single-arm meta-analysis - Li, Yulong; Su, Shen; Zhang, Mengwen; Yu, Limin; Miao, Xinyuan; Li, Hongjun; Sun, Yanping (Frontiers in Neurology, 2024)
Objective Antiseizure medications (ASMs) are first line therapy for seizure disorders. Their effects on arrhythmias, especially the risk of arrhythmias associated with lacosamide (LCM), levetiracetam (LEV), and perampanel (PER), have been intensely investigated. Methods We searched four databases (PubMed, EMBASE, Cochrane Library, and Web of Science) until August 6, 2023. We used a common effects model and reported data as pooled incidence with 95% CIs. Meta-analyses were conducted to elucidate the risk of arrhythmias with different drugs, and Egger’s regression was performed to detect publication bias analysis. Results We included 11 clinical trials with 1,031 participants. The pooled incidence of arrhythmias in the LEV group was 0.005 (95% CI: 0.001-0.013), while it was 0.014 in the LCM group (95% CI: 0.003-0.030). Publication bias analyses indicated no significant bias in the LEV group (t = 0.02, df = 4, p-value = 0.9852) but a significant bias in the LCM group (t = 5.94, df = 3, p-value = 0.0095). We corrected for this bias in the LCM group using the trim-and-fill method, which yielded a similar pooled incidence of 0.0137 (95% CI: 0.0036-0.0280), indicating good reliability. Due to insufficient studies, we could not conduct a meta-analysis for PER, and we analyzed them in our systematic review. Conclusion The use of LCM significantly elevated the risk of arrhythmias, while LEV had non-significant arrhythmogenic effects. As for the arrhythmogenic effects of PER, more clinical trials are needed in the future.